ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Kuswanti; Supriyadi, Edy; Wirawan (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2016)
This research is to test a theoretical model about the impact of the organizational climate as a result of servant leadership and conflict management towards organizational citizenship behavior with as mediator; the organizational commitment of PT Pegadaican (Pesero). The total number of respondents was 213 consisting of employees of the Central Office, the Jakarta I Area Office and the Jakarta II Area Office. To collect the data, the instrument utilized was a Linkert Technique scale questionnaire, after which the data was processed using a Lisrel 8.72 software version deploying applicative statistics using The Sructural Equation Model (SEM), and for analysis Confimatory Factor Analys Confimatory and Factor Analys technique was used. As the result it could be concluded that the hypothesis of the research is in accordance with the theoretical model about the impact of servant leadership, and conflict management on organizational citizenship behavior with as mediator the organizational commitment of the PT. Pegadaian (Pesero); the data did support this accordance and could be accepted. The same was the case for the structural equation hypotheses, and in general it could be concluded that the organizational climate created by servant leadership had a direct, positive and significant impact on organizational citizen behavior, and that conflict management had an direct positive but insignificant impact on organizational citizenship behavior. Furthermore, the organizational climate, servant leadership and conflict management had direct and positive impact on organizational commitment and the organizational climate, servant leadership and conflict management had an indirect, positive and significant impact on organizational citizenship behavior through the mediator of organizational commitment.